2006
DOI: 10.1109/jmems.2006.883581
|View full text |Cite
|
Sign up to set email alerts
|

Skin-Effect Self-Heating in Air-Suspended RF MEMS Transmission-Line Structures

Abstract: Air-suspension of transmission-line structures using microelectromechanical systems (MEMS) technology provides the effective means to suppress substrate losses for radio-frequency (RF) signals. However, heating of these lines augmented by skin effects can be a major concern for RF MEMS reliability. To understand this phenomenon, a thermal energy transport model is developed in a simple analytical form. The model accounts for skin effects that cause Joule heating to be localized near the surface of the RF trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…An efficient preconditioner was also developed to accurately solve the highly ill conditioned matrix system stemming from the extremely small electrical dimensions of RF MEMS [24]. We remark that the theoretical predictions resulting from the proposed integrated full-wave electromagnetic/thermal model are compared with experimental data [25] and found to be in good agreement.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…An efficient preconditioner was also developed to accurately solve the highly ill conditioned matrix system stemming from the extremely small electrical dimensions of RF MEMS [24]. We remark that the theoretical predictions resulting from the proposed integrated full-wave electromagnetic/thermal model are compared with experimental data [25] and found to be in good agreement.…”
Section: Introductionmentioning
confidence: 79%
“…The experimental data refer to a device subjected to an RF signal and can be used to validate our model predictions for the selfheating of an RF-MEMS switch in its 'up' state. The details of the design, fabrication and RF/thermal characterization of the testing device can be found in [25]. In brief, we measured the spatially averaged temperature increase in a MEMS RF structure at various frequencies and RF input power using a dc electrical resistance thermometry technique, specially developed for an RF setup.…”
Section: Experimental Validationmentioning
confidence: 99%
“…Already in 2000, Barker and Rebeiz [51] presented a design and optimization of distributed MEMS transmissionline (DMTL) phase shifters for the U-band and W-band with analogue tuning capability of the individual stages, fabricated on quartz substrate. (c) MEMS tunable dielectric-block loaded-line phase shifter Both the TTD network and the DMTL MEMS phase shifter concepts have the disadvantage that the capacitive MEMS switches or tunable capacitor, employed in both concepts, are composed of thin metal bridges that cannot handle large induced current densities at high RF power because of limited heat conductivity to the substrate due to their suspension above the substrate [53][54][55]. Measured phase shift per decibel loss was 70 /dB from 75 to 110 GHz.…”
Section: (B) Distributed Mems Transmission-line Phase Shifters (Dmtl)mentioning
confidence: 99%
“…Topologies presented in the literature are typically based on switched true-time delay-lines (TTD) or periodically capacitiveloaded transmission lines distributed MEMS transmission line (DMTL) [1,2]. Reliability issues and failure mechanisms have been discussed in [5,6]. In [1], Stehle et al demonstrated a 3-bit TTD phase shifter with a maximum phase shift of 3608 and an IL of 5.7 dB at 76.5 GHz (63.28/dB).…”
Section: Introductionmentioning
confidence: 99%